Cisplatin based therapy: the role of the mitogen activated protein kinase signaling pathway - Iman W. Achkar (Journal of Translational Medicine, 2018)
Abstract Cisplatin is a widely used chemotherapeutic agent for treatment of various cancers. However, treatment with cisplatin is associated with drug resistance and several adverse side effects such as nephrotoxicity, reduced immunity towards infections and hearing loss. A Combination of cisplatin with other drugs is an approach to overcome drug resistance and reduce toxicity. The combination therapy also results in increased sensitivity of cisplatin towards cancer cells. The mitogen activated protein kinase (MAPK) pathway in the cell, consisting of extracellular signal regulated kinase, c-Jun N-terminal kinase, p38 kinases, and downstream mediator p90 ribosomal s6 kinase (RSK); is responsible for the regulation of various cellular events including cell survival, cell proliferation, cell cycle progression, cell migration and protein translation. This review article demonstrates the role of MAPK pathway in cisplatin based therapy, illustrates different combination therapy involving cisplatin and also shows the importance of targeting MAPK family, particularly RSK, to achieve increased anticancer effect and overcome drug resistance when combined with cisplatin.